Proposal of a practice to conceive a minimum viable multimedia system (2021)
Different types of agile approaches and LEAN methodologies have guided the development of solutions based on a minimum viable product mainly from the product design and development body of the knowledge. However, these approaches offer generic practices for a wide variety of solutions. This study presents an original proposal that provides a vertical solution for the conception of a minimum viable multimedia system, with a practice expressed in the graphic notation language of Essence. The study presents a contribution through a case study related to the clarity about the flow of activities, techniques, and specific tools that the practitioners must use to define a minimum viable multimedia system. This work also contributes to the criteria unification of the teamwork to carry out the follow-up of the progress in realizing the activities necessary to complete the job needed for the conception of the minimum viable multimedia system, using an MS-value sub-alpha